المشكلات السكانية في الجمهورية العربية السورية من وجهة نظر عيّنة من الخبراء والمختصين "دراسة تحليلية ميدانية" (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
هدف البحث إلى تعرّف المشكلات السكانية في سورية من وجهة نظر عيّنة من الخبراء والمختصين في القضايا السكانية, وتعرّف الفروق في آراء عيّنة البحث حول درجة وجود المشكلات السكانية في سورية تبعاً للمتغيرات الآتية (الجنس، المؤهل العلمي، الخبرة), ولمعالجة مشكلة البحث استخدم المنهج الوصفي التحليلي, ولتحقيق أهدافه صُمّمت استبانة احتوت على (99) عبارة وزعت إلى ثمانية مجالات تضمنت المشكلات (الديموغرافية، الصحية، الأسرية، النوع الاجتماعي، التعليمية، الاقتصادية، المتعلقة بالبيئة والموارد، المتعلقة بالتنمية), واشتملت عيّنة البحث على (46) فرداً, وللتحقق من صدق الاستبانة، عُرضت على مجموعة مؤلفة من (7) محكمين مختصين في هذا المجال, وتم التأكد من ثباتها بتطبيقها على عيّنة شملت (20) فرداً، من خلال حساب معامل (Cronbach – Alpha) وقد بلغت قيمته (0.98)، وكذلك بلغ (0.83) عن طريق اختبار (Test - Retest). أظهرت النتائج أن (36.22%) من أفراد العيّنة وافقوا على وجود المشكلات المذكورة في الاستبانة في سورية، و(30.08%) وافقوا على وجودها قليلاً، في حين أن(24.52%) وافقوا على عدم وجودها، كما أن أكثر المشكلات السكانية التي تعاني منها سورية وجوداً هي المشكلات الديموغرافية, وتوصل البحث إلى وجود فروق ذات دلالة إحصائية تبعاً لمتغير (الخبرة)، وإلى عدم وجود فروق ذات دلالة إحصائية تبعاً لمتغيري (الجنس والمؤهل العلمي). The research aims to identify the problems of population in Syria, from the viewpoint of a sample of experts and specialists in this field. It aims to identify differences in views of the sample in the presence of population problems according to the following variables (sex, educational qualification, experience). To address the research problem, we use the analytical descriptive method. To achieve its objectives a questionnaire was designed, which contains (99) phrases which were distributed to eight main categories including the following problems: (demographic, health-care, family, gender, education, economic, environment and resources, development). To investigate the veracity of the questionnaire, it’s offered on a group of (7) specialists arbitrators in this field. Its stability was assured through applying it to the sample of (20) members, by calculating the coefficient (Cronbach - Alpha), the total value was of (0.98), as well as total of (0.83) by applying the  Test- Retest . The results show that (36.22%) of respondents agreed on the presence of the problems mentioned, and (30.08%) agreed to its presence a bit, while (24.52%) agreed not to its presence. The most population problems experienced is the demographic problems. The research finds that there are statistically significant differences depending on the variable of (experience), and there was no difference depending on the variables of (sex, educational qualification).